Megadisasters : the science of predicting the next catastrophe - Diacu, Florin, 1959-2018 (Princeton University Press, 2010)
Can we predict cataclysmic disasters such as earthquakes, volcanic eruptions, or stock market crashes? The Indian Ocean tsunami of 2004 claimed more than 200,000 lives. Hurricane Katrina killed over 1,800 people and devastated the city of New Orleans. The recent global financial crisis has cost corporations and ordinary people around the world billions of dollars. This is a book that asks why catastrophes such as these catch us by surprise, and reveals the history and groundbreaking science behind efforts to forecast major disasters and minimize their destruction. Each chapter of this book explores a particular type of cataclysmic event and the research surrounding it, including earthquakes, tsunamis, volcanic eruptions, hurricanes, rapid climate change, collisions with asteroids or comets, pandemics, and financial crashes. The author tells the harrowing true stories of people impacted by these terrible events, and of the scientists racing against time to predict when the next big disaster will strike. He describes the mathematical models that are so critical to understanding the laws of nature and foretelling potentially lethal phenomena, the history of modeling and its prospects for success in the future, and the enormous challenges to scientific prediction posed by the chaos phenomenon, which is the high instability that underlies many processes around us. Yielding new insights into the perils that can touch every one of us, this book shows how the science of predicting disasters holds the promise of a safer and brighter tomorrow.